Management and risk factor control of coronary artery disease in elderly versus nonelderly: A multicenter registry - Arintaya Phrommintikul (2018)
© 2016 JGC All rights reserved. Background Coronary artery disease (CAD) is a leading cause of death in elderly because aging is the important non-modifiable risk factors of atherosclerosis and also a predictor of poor outcomes. Underuse of guideline directed therapy may contribute to suboptimal risk factor control and worse outcomes in the elderly. We aimed to explore the management of CAD, risk factors control as well as goal attainment in elderly compared to nonelderly CAD patients. Methods The CORE-Thailand is an ongoing multicenter, prospective, observational registry of patients with high atherosclerotic risk in Thailand. The data of 4120 CAD patients enrolled in this cohort was analyzed comparing between the elderly (age ≥ 65 years) vs. nonelderly (age < 65 years). Results There were 2172 elderly and 1948 nonelderly patients. The elderly CAD patients had higher prevalence of hypertension, dyslipidemia, atrial fibrillation and chronic kidney disease. The proportion of patients who received coronary revascularization was not different between the elderly and nonelderly CAD patients. Antiplatelets were prescribed less in the elderly while statin was prescribed in the similar proportion. Goal attainments of risk factor control of glycemic control, low density lipoprotein cholesterol, and smoking cessation except the blood pressure goal were higher in the elderly CAD patients. Conclusions The CORE-Thailand registry showed the equity in the treatment of CAD between elderly and non-elderly. Elderly CAD patients had higher rate of goal attainment in risk factor control except blood pressure goal. The effects of goal attainment on cardiovascular outcomes will be demonstrated from ongoing cohort.